2000
DOI: 10.1007/s003440000007
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis Provides Evidence for Transient Initial Cells in Shoot Apical Meristems of Seed Plants

Abstract: Drift of mutated sectors in sectorial or mericlinal plant chimeras has been interpreted as indirect evidence of initial impermanence at the apex. However, the same effect may result from mutation in noninitial cells positioned close to the vertex of the apical dome. Clonal analysis of the cell packets present in the superficial layer of spruce and magnolia apices provided the library of patterns suggesting that the position and the number of initial cells, and in some cases also the meristem axis inclination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…However, those moving downwards to the rib zone may initially form calluses instead of shoots. It has been hypothesized that stem cells change over time, and that there are no permanent stem cells (Stewart and Dermen, 1970;Zago´rska-Marek and Turzan´ska, 2000). Our results contradict this hypothesis, clearly indicating cell lineages arising from single permanent stem cells.…”
Section: Transposition Activity In Meristem Tissuecontrasting
confidence: 82%
“…However, those moving downwards to the rib zone may initially form calluses instead of shoots. It has been hypothesized that stem cells change over time, and that there are no permanent stem cells (Stewart and Dermen, 1970;Zago´rska-Marek and Turzan´ska, 2000). Our results contradict this hypothesis, clearly indicating cell lineages arising from single permanent stem cells.…”
Section: Transposition Activity In Meristem Tissuecontrasting
confidence: 82%
“…The meristem continues its organogenic activity throughout the entire life of the axis, varying in seasonal activity and changing the identity of initiated lateral organs (e.g., leaves, scales, etc.). Three or four initial cells function in the SAM at any given moment, as shown in Picea [51], but initial cells may be impermanent and exchanged into different initials during the ontogeny of a particular shoot [51,52]. Leaves are initiated by periclinal divisions in the subsuperficial cells within the organogenic (peripheral) zone of the meristem [3].…”
Section: Gymnospermsmentioning
confidence: 99%
“…Leaves are initiated in the peripheral (organogenic) zone of the SAM due to periclinal divisions in the second and third layers of the tunica (Fig. 2g) [3]; the outermost layer of the tunica normally contains only three or four initial cells [51,70]. Attempts to identify correlations between the stability of the initial cells and the most common and stable phyllotaxes have revealed that the number and permanency of the initial cells in the tunica do not affect the phyllotactic pattern, which is formed at the meristem [70].…”
Section: Angiospermsmentioning
confidence: 99%
“…Cycads, ginkgo, Gnetales and conifers are gymnosperms. Apical meristems in these plants lack permanent initials (Zagorska‐Marek & Turzanska, 2000); thus diplontic selection may be more likely than in pteridophytes (Klekowski, Mohr & Kazarinova‐Fukshansky, 1986). Although clonal growth based upon extensive vegetative reproduction is not common in this group of plants, it should be noted that long‐lived trees, for which this group is noted, are essentially aerial clones.…”
Section: Vegetative Reproduction and Meristemsmentioning
confidence: 99%